Desigualdade das médias e a resolução de problemas geométricos - Rigodanzo, Mauro (2016)
The research presents some suggestions of activities for Mathematics teaching, in order to application of triangle inequality and inequality of the geometric, quadratic, arithmetic and harmonic mean to positive real numbers. These activities involve problems with plane geometry, spatial geometry and analytic geometry, using also the Dynamic Mathematics software, GeoGebra, in the illustration of the solutions. The choice of a computer application is justified because I believe that with its use, the perception of concepts and geometrical properties may be facilitated. In this way, it is expected that students can expand their skills in geometry and algebraic calculations. The study also points some researches related to the theme inequalities, contributing to the mathematics teaching.